2020
DOI: 10.3390/ijms21020475
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptor 2 Modulates Maturation of Dendritic Cells and Their Capacity to Induce Hapten-Induced Contact Hypersensitivity

Abstract: Contact hypersensitivity (CHS) is an established animal model for allergic contact dermatitis. Dendritic cells (DCs) play an important role in the sensitization phase of CHS by initiating T cell responses to topically applied haptens. The cannabinoid receptors 1 (CB1) and 2 (CB2) modulate DC functions and inflammatory skin responses, but their influence on the capacity of haptenized DCs to induce CHS is still unknown. We found lower CHS responses to 2,4-dinitro-1-fluorobenzene (DNFB) in wild type (WT) mice aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Human DCs express CB 1 and CB 2 receptors and also produce AEA and 2-AG [ 146 ], suggesting potential effects on the TME. CB 2 has been recently reported to influence dendritic cell maturation [ 230 ]. Another innate immune cell population with cannabinoid receptor expression is NK cells [ 16 ], which are well linked to tumor regression [ 231 ].…”
Section: The “Immune Endocannabinoid System” In Adaptive and Innatmentioning
confidence: 99%
“…Human DCs express CB 1 and CB 2 receptors and also produce AEA and 2-AG [ 146 ], suggesting potential effects on the TME. CB 2 has been recently reported to influence dendritic cell maturation [ 230 ]. Another innate immune cell population with cannabinoid receptor expression is NK cells [ 16 ], which are well linked to tumor regression [ 231 ].…”
Section: The “Immune Endocannabinoid System” In Adaptive and Innatmentioning
confidence: 99%
“…Topical cannabinoids can be associated with cutaneous adverse events, such as allergic contact dermatitis and contact urticaria (Table 8) [10][11][12][13][14][15][16]. A study of dispensaries in Los Angeles, California, discovered that 84% of over-the-counter topical cannabinoids had one or more North American contact dermatitis group (NACDG) allergens [17].…”
Section: Kaposi Sarcomamentioning
confidence: 99%
“…Several studies demonstrated that human DCs expressed CBRs and produced eCBs [ 12 , 251 ]. In the pancreatic ductal adenocarcinoma murine model, 2-AG administration exhibited a direct anti-tumour effect by inducing DC phenotypic maturation and the production of pro-inflammatory cytokines, but also significantly promoted an immunosuppressive microenvironment via increasing the suppressive immune cell population of myeloid-derived suppressor cells (MDSCs) [ 252 ].…”
Section: The Involvement Of the Endocannabinoid System In The Tumour Microenvironmentmentioning
confidence: 99%